1990
DOI: 10.1093/ajcn/51.4.665
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and hemodynamic effects of magnesium supplementation in patients with essential hypertension

Abstract: The effect of magnesium supplementation on blood pressure, erythrocyte cation metabolism, and serum lipids was evaluated in 13 patients with mild hypertension. After randomization and a 3-wk placebo run-in period, seven patients received 40 mmol Mg aspartate (20 mmol elemental Mg twice daily) and six received placebo for 3 mo. In comparison with placebo treatment, magnesium aspartate therapy had no effect on blood pressure, lipid concentrations, or erythrocyte cation metabolism. These results demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…Furthermore, supplementation of the usual diet with additional Mg ( $ 10 mmolad) for a 28 d period had no signi®cant effect on serum Mg concentration. This is in agreement with the ®ndings of other studies which show that serum Mg in healthy subjects was unaffected by Mg supplementation (Zemel et al, 1990;Geleijnse et al, 1994;Plum-Wirell et al, 1994;Witteman et al, 1994), con®rming that serum Mg concentration is tightly regulated, even when Mg intake is higher than normal.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, supplementation of the usual diet with additional Mg ( $ 10 mmolad) for a 28 d period had no signi®cant effect on serum Mg concentration. This is in agreement with the ®ndings of other studies which show that serum Mg in healthy subjects was unaffected by Mg supplementation (Zemel et al, 1990;Geleijnse et al, 1994;Plum-Wirell et al, 1994;Witteman et al, 1994), con®rming that serum Mg concentration is tightly regulated, even when Mg intake is higher than normal.…”
Section: Discussionsupporting
confidence: 92%
“…However, intervention studies with Mg therapy in hypertensives and normotensives have led to con¯icting results. Several studies in hypertensives and normotensives have shown a blood pressure lowering effect of Mg supplements (in hypertensives, Dyckner & Wester, 1983;Saito et al, 1988;Motoyama et al, 1989;Geleijnse et al, 1994;Witteman et al, 1994;in normotensives, Itoh et al, 1997), while others have not (in hypertensives, Cohen et al, 1984;Cappuccio et al, 1985;Henderson et al, 1986;Zemel et al, 1990;Durlach et al, 1992;Haga, 1992;Kisters et al, 1993;Plum-Wirell et al, 1994;Sacks et al, 1995;in normotensives, Haga, 1992;Yamamote et al, 1995;Sacks et al, 1998). Therefore, the effect of oral Mg supplementation on blood pressure remains controversial and especially, in normotensives where data is limited.…”
Section: Introductionmentioning
confidence: 99%
“…The average reduction in BP based on an effect size of 0.36 for DBP and 0.32 for SBP translate to an actual reduction of 2 --3 mm Hg for DBP and 3 --4 mm Hg for SBP. At the lower dosage 24 the effect sizes for SBP and DBP were 0.87 and 1.03, respectively, whereas at the higher dosage 25 effect sizes were seen to be À1.53 and À0.57, although Zemel et al's 25 work was anomalous to other higher-dosage studies. The overall effect size for DBP was slightly higher than that for SBP.…”
Section: Discussionmentioning
confidence: 85%
“…Those using o370 mg demonstrated high levels of variation. One anomaly for this was the study by Zemel et al, 25 which used the highest dosage of 973 mg Mg/day but showed wide CI limits (DBP 95% CI À1.69 to 0.55, SBP À2.83 to À0.23) and a low effect size of À0.57 and À1.53 for DBP and SBP, respectively. This may be attributed to the small cohort size (n ¼ 13) or to study design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation